Environmental factors on I.Q. - Pallomina, Maria Leda U. (1998)
This study involved 36 U.P. college students, who were deliberately selected from three randomly chosen course classes, with a total number of 125 students from U.P. Tacloban College, Tacloban City. This research was conducted to examine whether home environment and socioeconomic status has significant effects on I.Q. For this, three research instruments were distributed, thus a demographic profile form, a home environment classification test (a self-inventory test) and the Otis-Lenon School Ability Test (an IQ test of 80 items, that is, good for 40 minutes) among 125 students. Since there were two variables, namely the home environment and socioeconomic status, considered in this study, a 2x3 factorial design was used. Each subtype of the first factor was composed of 18 subjects and each subtype of the second variable was comprised of 12. It was found out that each variable was significant on IQ at the .05 level of significance. However, their interaction effect was nonsignificant at .05 level. Therefore, the impact of the two variables when combined was insignificant, unlikely when they were taken separately.